1992
DOI: 10.3928/0147-7447-19920801-06
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Tendon Ends After Achilles Tendon Repair: A Prospective, Randomized, Multicenter Study

Abstract: Fifty-seven patients treated for an acute rupture of the Achilles tendon were studied. The patients were randomized into a Mason suture technique or a reinforced continuous six-strand suture technique, and markers were attached to each tendon end perioperatively. The postoperative separation of the markers was studied by repeat radiographic examination. Despite immobilization, separation developed after a Diphasic course, and after 7 weeks the mean separation was 10.5 mm. No difference was found between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 8 publications
3
22
0
1
Order By: Relevance
“…This was supported by the high ATRS values at 6 and 12 months. Achilles tendon lengthening with tendon end separation has been reported to occur primarily during the first 4 months after surgery [6,9,17]. Of clinical relevance, the clinical outcome has been reported to correlate with the degree of tendon elongation [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by the high ATRS values at 6 and 12 months. Achilles tendon lengthening with tendon end separation has been reported to occur primarily during the first 4 months after surgery [6,9,17]. Of clinical relevance, the clinical outcome has been reported to correlate with the degree of tendon elongation [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive tendon elongation and rerupture are also described as two of the reasons for surgical revision following ATR [14, 35]. Studies have demonstrated that after Achilles tendon repair, tendon ends may separate [19]. Kangas et al [8] have also shown that early motion resulted in a lesser degree of tendon separation than did immobilization after surgical treatment of an ATR.…”
Section: Discussionmentioning
confidence: 99%
“…However, we lacked measurements on tendon elongation before the 2-week follow-up, and a substantial amount of total tendon elongation could have occurred before bead insertion. 29,31 This study had some limitations. In the measurements of the material properties, a number of simplifying assumptions had to be made, such as tissue homogeneity, a consistent cross-sectional area along the tendon between the beads, and a linear load deformation relationship.…”
Section: Discussionmentioning
confidence: 95%
“…However, we lacked measurements on tendon elongation before the 2-week follow-up, and a substantial amount of total tendon elongation could have occurred before bead insertion. 29 , 31 …”
Section: Discussionmentioning
confidence: 99%